2002
DOI: 10.1080/028275802753742882
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drought on Growth and Mortality of Actively Growing Norway Spruce Container Seedlings Planted in Summer

Abstract: Effect of drought on growth and mortality of actively growing Norway spruce container seedlings planted in summer.Survival, root egress and height growth of 13-month-old actively growing Norway spruce (Picea abies (L.) Karst.) container seedlings exposed to preplanting drying treatments (0, 4, and 8 days) and postplanting drought periods (1, 2, 3, and 4 weeks) were studied in the eld between 5 July and 18 August 1999. The mortality of seedlings increased and the height growth and root egress decreased througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 14 publications
4
28
2
Order By: Relevance
“…Consequently, water stress did not hamper seedlings in maintaining a strong apical dominance to achieve the required rates of height growth, although to the detriment of lateral shoot lengthening (O'Connel and Kelty 1994). Similar results were also found in Finland for Picea abies seedlings, whose growth in height was not affected by a drought period shorter than 3 weeks (Helenius et al 2002).…”
Section: Discussionsupporting
confidence: 74%
“…Consequently, water stress did not hamper seedlings in maintaining a strong apical dominance to achieve the required rates of height growth, although to the detriment of lateral shoot lengthening (O'Connel and Kelty 1994). Similar results were also found in Finland for Picea abies seedlings, whose growth in height was not affected by a drought period shorter than 3 weeks (Helenius et al 2002).…”
Section: Discussionsupporting
confidence: 74%
“…C25 had the lowest root density compared to seedlings of the bigger sizes, indicating that in proportion, a higher volume of soil was available for the roots of smaller seedlings, which have lower needle biomass and consequently need less water for the evapotranspiration process (Helenius et al 2002(Helenius et al , 2005. The lower shoot:root ratio of smaller seedlings could also explain their ability to sustain an appropriate water status of the tissues.…”
Section: Factors Affecting Drought Tolerancementioning
confidence: 99%
“…Heikinheimo (1941), in Finland, and Mork (1951), in Norway, have demonstrated that planting Norway spruce bare-root seedlings is possible, but drought in some years may markedly reduce the survival of seedlings. The roots of container seedlings are not as dry-sensitive as bare-root seedlings, and drought is not a particularly high risk (Helenius et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%